CHANGING PICTURE OF KATHAK DANCE: बदलती तस्वीर कथक नृत्य की - Singh, Monika (International Journal of Research -GRANTHAALAYAH, 2015)
What was yesterday becomes old today and what is to come tomorrow also remains a saga of the past for a few days. With the speed at which time is moving, the wave of change is moving at the same speed. At present, the field of dance is also not untouched by it. Changes and innovation in the region have demonstrated this in many ways. Kathak dance existing since ancient times was a dance form full of religion and spirituality. Kathak dance is considered to have originated by the narrators having narrated the acting by the storytellers during the Bhajan-Kirtan in the temples. जो कल था, वह आज पुराना हो गया और जो कल आनेवाला है वह भी कुछ ही दिनों से अतीत की गाथा बनकर रह जाता है। समय जिस गति से आगे बढ़ रहा है, उसके साथ परिवर्तन की लहर भी उतनी ही गति से प्रवहमान है। वर्तमान समय में नृत्यकला का क्षेत्र भी इससे अछूता नहीं है। इस क्षेत्र में परिवर्तन और नवाचार ने इसे कई रूपों में प्रदर्शित किया है। प्राचीनकाल से विद्यमान कत्थक नृत्य धर्म-अध्यात्म से परिपूर्ण नृत्य शैली थी। मंदिरों में भजन-कीर्तन के समय कथावाचकों के द्वारा अभिनय युक्त कथा कहने से कत्थक नृत्य की उत्पत्ति मानी जाती है।